2015
DOI: 10.1001/jamasurg.2014.1756
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing Disparities in the Age-Related Incidences of Colon and Rectal Cancers in the United States, 1975-2010

Abstract: Importance The overall incidence of colorectal cancer (CRC) has been decreasing since 1998, but there has been an apparent rise in the incidence of CRC in young adults. Objective To evaluate age-related disparities in secular trends in CRC incidence in the United States. Design A retrospective cohort study using the Surveillance, Epidemiology, and End Results (SEER) CRC registry. Age at diagnosis was analyzed in 15-year intervals starting at the age of 20. SEER*Stat was used to obtain the annual cancer inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
731
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 854 publications
(768 citation statements)
references
References 19 publications
21
731
1
15
Order By: Relevance
“…We found that age‐adjusted invasive CRC incidence rates in younger adults (20‐49) have risen significantly since the mid‐1990s in NJ, similar to the increase in US younger adults 1, 2, 3, 4, 5, 6. This contrasts with older adults (≥50) in NJ and the US whose CRC incidence rates have declined significantly for several decades 1, 2, 3, 4, 5, 6.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…We found that age‐adjusted invasive CRC incidence rates in younger adults (20‐49) have risen significantly since the mid‐1990s in NJ, similar to the increase in US younger adults 1, 2, 3, 4, 5, 6. This contrasts with older adults (≥50) in NJ and the US whose CRC incidence rates have declined significantly for several decades 1, 2, 3, 4, 5, 6.…”
Section: Discussionmentioning
confidence: 62%
“…This contrasts with older adults (≥50) in NJ and the US whose CRC incidence rates have declined significantly for several decades 1, 2, 3, 4, 5, 6. CRC incidence rates are increasing the fastest among the youngest adults ages 20‐39.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, age is a very powerful predictor for the development of precursor adenomas and CRC, with approximately 94.5 % of all CRCs occurring after age 50, the age at which universal CRC screening is recommended for men and women [2], although 5.5 % of all CRCs occur before age 50, when general screening is not offered or recommended unless there is a strong family history of CRC, when screening is recommended to commence at age 40 [2,3]. Over a 25-year period in a cohort of nearly 400,000 CRC patients, the incidence of CRC was reduced by 0.92 %, although this decline only occurred in subjects [age 50, and largely attributed to screening implementation [5]. Following current trends, the incidence of colon and rectal cancer are projected to increase 124 and 90 % in subjects aged 20-34 and 27.7 and 46.0 % in subjects aged 35-49, respectively, by 2030 [5], with rectal cancer diagnosed in about two-thirds of patients \50 years [6].…”
mentioning
confidence: 99%